The trajectory of the network of studies on the implementation of educational public policies - de Oliveira, Breynner Ricardo; Silva Fernandes, Fabiana; Prado de Oliveira, Ana Cristina; Muylaert Lima, Naira da Costa (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: this article presents the trajectory of the development of a network of researchers that emerged in Brazil to deepen and expand a more recent strand of analysis of educational public policies, the analysis of policy implementation. REIPPE is a social network that brings together researchers and, more recently, managers, other education professionals, and graduate students interested in a particular field of knowledge. Originality/contribution: The contribution is the sharing of a network organization experience, which aims to stimulate further studies on the different ways of grouping researchers, which has been strengthened in recent years with the creation of research groups, research in groups, collaborative networks, networks of researchers and observatories. Method: this is an experience report, with a historical approach, which sought to rescue the reasons why the network was formed and how it has been constituted since 2014, the year of its creation. The course of existence of the network was elaborated from its creation; its dynamics and identity; strategies to institutionalize; governance mechanisms; the promotion of activities aimed at strengthening the countryside in Brazil; the dissemination of content and the engagement of the interested public. Strategies/information collection: a documentary survey was carried out based on the following sources: (1) two management reports produced by the network (2019-2020) and (2020-2021); (2) visits to your website; (3) visits to your Facebook page and YouTube channel; (4) academic production linked to research associated with its members (theses, dissertations and indexed articles); (5) Minutes of Meetings and (6) Personnel Records. Conclusions: The analysis of the compiled data reveals that, since its foundation, the network has been strengthened and become a reference for researchers who deal with the issue of implementation, bringing together theoretical perspectives and research methodologies for the study of policies and programs in the field of education. The data also indicate that the network's activity has grown (accesses, clicks, and the number of subscribers), along with its academic production, reflecting in the increased engagement of the interested public, including organizations that finance and implement educational programs.